Cuba straits [large type] - White, Randy Wayne (White, Randy Wayne. Doc Ford series., 2015)
"Doc Ford's old friend, General Juan Garcia obtains and sells a collection of letters written by Fidel Castro between 1960-62 to a secret girlfriend. When both Garcia and the who bought the letters disappear, Doc Ford investigates, convinced that those letters contain a secret that someone, or some powerful agency, cannot allow to be made public"--